Digital Rupiah as a Proponent of Financial Inclusion: A Study of Legal Strengthening Aspects - Ayu Purnamawati, Shinta; Kharisma Nuryasinta, Radhityas; Ramdhani Setyawan, Fadjar; Alam, Syariful; Luthfi, Muhammad; Adhial Fajrin, Yaris; Puspitasari Wardoyo, Yohana (KnE Social Sciences, 2024)
The public’s need for a payment system that is fast and inexpensive but also secure, inspired Bank Indonesia to create a digital currency known as the Digital Rupiah. The basis for Bank Indonesia’s consideration of launching the Digital Rupiah is to carry out its mandate in the digital era in the form of legal digital payment instruments so that it can become a means of supporting financial innovation. However, the potential for Digital Rupiah as financing inclusion or exclusion is also a crucial matter that needs to be studied in more depth. This study uses a type of normative legal research with data sources through library research, which will analyze the potential for financial inclusion and exclusion and examine the strengthening of the Digital Rupiah from a legal perspective. The results of this study indicate that there is still potential for financial exclusion posed by Digital Rupiah, therefore a strategy is needed to open up opportunities for financial inclusion from Bank Indonesia, regulators, ministries, and other institutions in efforts to provide financial services to the wider communities. This also includes supporting greater digital economic and financial integration that are equitable and sustainable for all the people. The provisions for Digital Rupiah that have been embedded in the P2SK Law are still minimal because the provisions for managing them have not been fully explained. So it is necessary to strengthen the regulation of several aspects so that Digital Rupiah can become a financial inclusion requirement. Keywords: digital Rupiah, financial inclusion, legal reinforcement